2019
DOI: 10.31742/ijgpb.79.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, genotype × environment interaction and correlation analysis for grain iron and zinc contents in recombinant inbred line population of pearl millet [Pennisetum glaucum (L). R.

Abstract: Micronutrient malnutrition is one of the major health problem, especially iron (Fe) and zinc (Zn) deficiencies that are widespread coupled with inadequate food supply in the developing world. Pearl millet grains are a good source of Fe and Zn elements making it a potential staple crop for overcoming hidden-hunger and micronutrient deficiencies. Breeding pearl millet with high levels of grain Zn and Fe contents represents a major opportunity to enhance the intake of these minerals for poor and malnourished peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…Higher range, more diversity Index and large differences in mean values for most of the characters revealed that sufficient diversity existed among the genotypes and traits. The present findings were similar with previous reports in pearl millet (Dapke et al, 2014;Anuradha et al, 2018;Sharma et al, 2018 andMahendrakar et al, 2019).…”
Section: Genetic Diversity Analysissupporting
confidence: 94%
“…Higher range, more diversity Index and large differences in mean values for most of the characters revealed that sufficient diversity existed among the genotypes and traits. The present findings were similar with previous reports in pearl millet (Dapke et al, 2014;Anuradha et al, 2018;Sharma et al, 2018 andMahendrakar et al, 2019).…”
Section: Genetic Diversity Analysissupporting
confidence: 94%
“…e values were low for grain yield (˂30%), medium for 1000-grain weight (56.01%) and grain Fe (57.99%), and very high (˃60%) for the other traits. Similar results of high heritability for grain Fe content have been reported by [48]. Although [31] argued that broadsense heritability alone cannot be relied upon to achieve full genetic gain through selection, [50] maintained that the amount of progress in selection of a trait of interest is influenced by heritability estimates and hence can be relied upon for selection for specific trait improvement.…”
Section: Resultssupporting
confidence: 72%
“…Genotypic variance (σ 2 g) contributed a greater proportion of the phenotypic variance (σ 2 p) of majority of the traits and was 1.4-4.7 times that of the genotype × environment interaction variance (σ 2 g × e), indicating wide genetic variations among the genotypes for these traits and confirming the fact that these traits were largely controlled by genetic factors (Table 5). Recent studies reported similar genotype × environment interaction for pearl millet grains Fe and Zn and sesame [40,[47][48][49]. In the current studies, σ 2 p for grain yield showed that σ 2 g × e was 2.9 times σ 2 g, indicating that yield is greatly influenced by both genotype and environment interaction, though the environmental component exerted a disproportionally large influence than the genotypic component.…”
Section: Resultssupporting
confidence: 65%
“…In pearl millet, the bioavailability of Fe can be assumed to be 7.0–7.5% (Govindaraj et al, 2019 ). Approximately 50–100% of the daily requirement of iron can be met out with one meal of biofortified high-iron variety and is sufficient enough to overcome deficiency of iron in children, women and men (Kodkany et al, 2013 ; Mahendrakar et al, 2019 ).…”
Section: Nutritional Securitymentioning
confidence: 99%